Integral geographical study of the basin of the Omas river (Asia) - Comeca Chuquipul, Miguel Ángel (2007)
The spatial planification and his tool to utilized in our country implicate to the hidrografic basin like units to analysis. In this investigation could do the analysis to the physical, social, economic aspect of the basin to Omas’s river to specially locate and explain the potentials, the principals problems and limitations for example poverty to naturals resource, deficit to equipment to service, migration to the people and poverty present to the state. In this investigation to do emphasis to district to Coayllo, because in this place to summarize the problematic of the basin.